Terahertz waveguides for 6G communication - Mikhail Maneck Shah (Nanyang Technological University, 2022)
As the world continues to advance technologically at a rapid rate, the need for high speed data is increasing exponentially. 5G networks are being phased into our lives and possess numerous novel applications in a wide variety of industries. However, it will not be able to keep up with the rate of technological advancements for long with its limitations of spectral bandwidth. This is where 6G networks would come in to provide a long term solution.